1967
DOI: 10.1042/bj1030090
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of mucopeptide synthesis by benzylpenicillin in relation to irreversible fixation of the antibiotic by staphylococci

Abstract: 1. Benzylpenicillin is irreversibly fixed to staphyloccoci by a reaction that obeys second-order kinetics, whereas the progress of inhibition of mucopeptide synthesis obeys first-order kinetics after a short lag during which the antibiotic has no effect. 2. When the micro-organisms are saturated with benzylpenicillin they can still make mucopeptide in solutions containing chloramphenicol at a normal rate after a lag period. 3. About 90% of the benzylpenicillin stays fixed to the cells after mucopeptide synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

1968
1968
1983
1983

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 23 publications
3
33
0
Order By: Relevance
“…The binding followed saturation type kinetics (specific binding), and its saturation was achieved at low concentration (2 nmol/ mil) of the antibiotic, as has been shown (16,26) for penicillin-susceptible organisms. However, the binding to whole cells of this organism was entirely of the nonsaturation type (nonspecific), although binding to penicillin-susceptible organisms was specific as previously desciKbed (4,5,8,15,20,24,26), and saturation was achieved at low concentration of penicillin G, as with the membrane fractions (16,17). About 3 nmol of penicillin G was specifically bound per g of the membrane protein at saturation.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The binding followed saturation type kinetics (specific binding), and its saturation was achieved at low concentration (2 nmol/ mil) of the antibiotic, as has been shown (16,26) for penicillin-susceptible organisms. However, the binding to whole cells of this organism was entirely of the nonsaturation type (nonspecific), although binding to penicillin-susceptible organisms was specific as previously desciKbed (4,5,8,15,20,24,26), and saturation was achieved at low concentration of penicillin G, as with the membrane fractions (16,17). About 3 nmol of penicillin G was specifically bound per g of the membrane protein at saturation.…”
Section: Discussionmentioning
confidence: 88%
“…However, the binding was entirely nonspecific. The amount bound to whole cells was directly proportional to the concentration up to a level of at least 750 nmol/ml, although binding to the membrane fraction from this organism and to the whole cells of penicillin-susceptible organisms was specific as described above and previously (4,5,8,15,20,24,26). The binding of [14C]benzylpenicilloic acid to the cells was also nonspecific and of lower affinity compared with penicillin G.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The washing procedures employed were judged to be adequate to remove noncovalently bound "4C-penicillin G for the following reasons: (i) cells first saturated with "2C-penicillin G and then incubated with 14C-penicillin bound 5 counts per min per ml (corrected for reduction of specific activity), whereas a control sample incubated with "-C-penicillin G bound 498 (10,17). Rogers (17) reported that the binding reaction is temperature-sensitive and obeys second-order reaction kinetics for the first 20 min. These results were confirmed in this laboratory ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…More than 2000 counts were collected per sample. For counting liquid samples a dioxane-based scintillation fluid was used (Rogers, 1967). Estimation of the specijk activity of amino sugars.…”
Section: Wall Synthesis By Rod Mutants 337mentioning
confidence: 99%